Pengaruh Persepsi Harga dan Inovasi Produk terhadap Keputusan Pembelian Smartphone Xiaomi - Nova Aditya Pradana; Ugy Soebiantoro (Jurnal E-Bis, 2023)
In the era of digitalization of communication as it is today, the development of communication technology such as smartphones is growing rapidly following consumer needs. This study was conducted to identify the impact perceived price and product innovation towards purchase decision of Xiaomi Smartphone in Surabaya. This research is quantitative and uses primary data obtained through questionnaire distribution and additional data sourced from the official website of an institution or previous research. The sample in the research used accidental sampling with 100 respondents who were located in Surabaya. Primary data analysis in this research was supported by SmartPLS 4.0 software. The results of this research indicate that eprception towards price has a significant impact on purchasing decisions, while product innovation also has a significant impact on purchasing decisions for Xiaomi in Surabaya.